Code Switching Used by The Characters in “Susah Sinyal” Movie - Febi, Febi; Rahayuni, Ni Ketut Sri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study is entitled "Code Switching Used by The Characters in Susah Sinyal Movie". The discussion is aimed at finding out the type of code switching and analysing the function of code switching in the movie entitled "Susah Sinyal" The data source was taken from Susah Sinyal movie and this is a qualitative research with note taking techniques. The results of the data types of code switching obtained were analyzed using the theory of Poplack (1995) and the function were analyzed using the theory of Apple and Muysken (1987). This analysis is presented using an informal method. Research revealed that there are three types of code switching that were used by the characters. Those are tag switching, inter-sentential switching, and intra- sentential switching. For the functions of code switching, there are six functions found in the movie. Those are referential, directive, phatic, expressive, metalinguistic and poetic that are used by the characters in the movie.